Subharmonic almost periodic functions - Rakhnin, A. V.; Favorov, S. Yu. (Журнал математичної фізики, аналізу, геометрії, 2005)
We prove that almost periodicity in the sense of distributions coincides with almost periodicity with respect to Stepanov's metric for the class of subharmonic functions in a strip $\{z\in\mathbb{C}: a< Im z<b\}$. We also prove that Fourier coeficients of these functions are continuous functions in Imz. Further, if the logarithm of a subharmonic almost periodic function is a sub- harmonic function, then it is almost periodic. Mathematics Subject Classification: 42A75, 30B50.